Neuroprotective effects of γ-Aminobutyric acid-enriched germinated riceberry extract in cerebral ischemic reperfusion-induced cognitive impairment mice - Payungsak Tantipaiboonwong, Komsak Pintha, Napapan Kangwan, Dej Mann, Prathakphong Riyamongkhol, Watcharaporn Preedapirom Jeefoo (Journal of Applied Pharmaceutical Science, 2024)
This study investigates the neuroprotective effects of riceberry (RB) and germinated riceberry (GRB) extracts on cognitive impairment induced by cerebral ischemia-reperfusion (IR) injury. Our findings indicate that the germination process reduces total phenolic content and total antioxidant capacity, accompanied by a decline in antioxidant activity. However, the enriched γ-aminobutyric acid (GABA) content significantly increased in the GRB extract, reaching an 11.55-fold higher concentration than the RB extract. Male ICR mice were used in this study and received RB (500 mg/kg BW) or GRB (250 and 500 mg/kg BW) extracts for 28 days, with cerebral IR injury induced on day 21. Memory and learning were assessed using the Morris water maze on days 22–27 and novel object recognition on day 28. Both RB and GRB extracts improved spatial and recognition memory while reducing hippocampal malondialdehyde levels, indicating decreased oxidative stress. GRB demonstrated superior effects, displaying accelerated learning responses and enhanced retention of spatial memory. The study highlights the potential of GRB, attributed to its high GABA content, in mitigating cognitive impairment induced by cerebral IR injury. Further research is needed to explore the underlying mechanisms and optimize therapeutic applications.
Keywords: Germinated riceberry extract, Y-aminobutyric acid, cerebral ischemic-reperfusion, neuroprotective effects, cognitive impairment